Investigation on an innovative hydrocarbon sensor for real drive emissions - Muhammad Nor Azril, Zulkafli; Norazlianie, Sazali; Saiful Anwar, Che Ghani; Maurice, Kettner (Penerbit Akademia Baru, 2021)
European law specifies limit values (and test methods) for pollutant emissions from light duty vehicles and heavy-duty engines including carbon monoxide (CO), hydrocarbons (HC), nitrogen oxide (NOx) and particulates, which are considered dangerous to human health. The internal combustion engines nowadays have strict regulation for emissions that resulted in the growth of demands for measuring methods and the measuring technology. WLTC is a new procedure that replaced the existing New European Diving Cycle (NEDC) to make the emissions become more effective when do the test in laboratory or in real traffic driving. The aim of this research is to investigate suitability of the sensor principle for HC measurement based on tests and their evaluations. The hydrocarbon sensor used to detect the HC by thermal ionization, which produces an ion current as the output voltage of the sensor. The results obtained by the ion measurement concept show that the optimization of the combustion process can be developed through simple mean.